Multislice CT angiography in cardiac imaging. Part II: Clinical applications in coronary artery disease - Sun, Z.; Ng, K.H. (2010)
Multislice computed tomography (CT) angiography represents a technological evolution in cardiac imaging due to improved spatial and temporal resolution. Rapid improvements in multislice CT scanners over the last decade have allowed this technique to become a viable and effective alternative to invasive coronary angiography in selected patients. Multislice CT angiography has demonstrated high sensitivity and specificity, and in particular, a very high negative predictive value, which makes it a valuable imaging modality for screening patients suspected of coronary artery disease. In addition, multislice CT angiography demonstrates accuracy in the detection and characterisation of coronary plaques, and it has been reported to play an important role in predicting disease progression and cardiac events. The aim of this review was to present an overview of the clinical applications of multislice CT angiography in coronary artery disease, with regard to its diagnostic accuracy and predictive value in coronary artery disease. Emerging areas of multislice CT, including dual-energy CT and CT myocardial perfusion, are also discussed. Limitations of multislice CT angiography and future directions of cardiac multislice CT are highlighted.